2022
DOI: 10.3389/fimmu.2022.917905
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of IgA, IgG, and Neutralizing Antibody Responses Following Immunization With Moderna, BioNTech, AstraZeneca, Sputnik-V, Johnson and Johnson, and Sinopharm’s COVID-19 Vaccines

Abstract: In an ongoing multinational trial, we obtained blood samples from 365 volunteers vaccinated with mRNA vaccines (Moderna, BioNTech), viral DNA-vectored vaccines (AstraZeneca, Sputnik-V, and Johnson and Johnson), or the attenuated virus vaccine from Sinopharm. After collecting reactogenicity data, the expression of S-Protein binding IgG and IgA was analyzed using an automated sandwich ELISA system. Serum neutralizing potentials were then investigated using an ACE-2-RBD neutralizing assay. Moderna’s vaccine induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 48 publications
7
39
0
Order By: Relevance
“…The faster drop rate of anti-RBD compared to anti-S Ab levels could similarly be explained by a narrower anti-RBD Ab repertoire, targeting a restricted number of epitopes compared to those on trimeric Spike ectodomain. While the RC index has been shown to be significantly higher in cohorts of vaccinees receiving either mRNA or adenovirus vector-based COVID-19 vaccines compared to infected individuals, several hypotheses have been made trying to explain this fastest decline, such as the lack in number and diversity of memory B-cells and of bone marrow plasma cells [ 28 , 29 ]. According to our data, although the first vaccine dose resulted in a positive RC index, specifically for anti-S Abs, a significant increase in the RC index for anti-RBD Abs was especially observed between Day21 and Day42, reflecting the importance of the second vaccine dose for the efficient production of anti-RBD Abs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The faster drop rate of anti-RBD compared to anti-S Ab levels could similarly be explained by a narrower anti-RBD Ab repertoire, targeting a restricted number of epitopes compared to those on trimeric Spike ectodomain. While the RC index has been shown to be significantly higher in cohorts of vaccinees receiving either mRNA or adenovirus vector-based COVID-19 vaccines compared to infected individuals, several hypotheses have been made trying to explain this fastest decline, such as the lack in number and diversity of memory B-cells and of bone marrow plasma cells [ 28 , 29 ]. According to our data, although the first vaccine dose resulted in a positive RC index, specifically for anti-S Abs, a significant increase in the RC index for anti-RBD Abs was especially observed between Day21 and Day42, reflecting the importance of the second vaccine dose for the efficient production of anti-RBD Abs.…”
Section: Discussionmentioning
confidence: 99%
“…One more parameter that significantly affects post-vaccination anti-viral IgG and IgA kinetics is the type of the vaccine, as different candidates are globally available. Studies on different vaccine types report that mRNA vaccines induced the highest amount of anti-S IgG and IgA Abs and a high serum neutralization potential when compared to vector based vaccines (e.g., Astra Zeneca, Janssen, Sputnik-V) or vaccines using whole inactivated SARS-CoV-2 viral particles (Sinopharm) [ 29 ]. All types of vaccination also induced spike-specific IgA secretion, indicating individual mucosal immunity against SARS-CoV-2 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 12 In a recent study, it was revealed that that Sinopharm vaccine has relatively lower performance in terms of producing IgG antibodies and other parameters as well. 13 In return, the higher immune response could trigger unintended adverse reactions through immune enhancement in various parts of body. This explains the relatively lower inflammatory adverse events including ocular ones, reported after inactivated vaccines.…”
Section: Discussionmentioning
confidence: 99%